2012
DOI: 10.1111/j.1439-0264.2012.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Cross‐Sectional Anatomy of the Metatarsus and Digits of the One‐humped Camel (Camelus dromedarius) and Buffalo (Bos bubalis)

Abstract: The purpose of the present study was to provide a detailed computed tomography (CT) and cross-sectional anatomic reference of the normal metatarsus and digits for the camel and buffalo, as well as to compare between metatarsus and digits in these animals to outstand a basis for diagnosis of their diseases. Advantages, including depiction of detailed cross-sectional anatomy, improved contrast resolution and computer reformatting, make it a potentially valuable diagnostic technique. The hind limbs of 12 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 11 publications
7
30
0
Order By: Relevance
“…Moreover, these marrow cavities appeared hypodense and black in colour. Similar observations were reported in buffalo and camel (El-Shafey & Kassab, 2012), buffalo and cattle (Al-AKraa, El-Kasapy, & El-Shafey, 2014), cattle (Raji et al, 2008) and camel (Badawy, 2011;El-Shafey & Sayed-Ahmed, 2012;Ibrahim et al 2019aIbrahim et al , 2019b.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, these marrow cavities appeared hypodense and black in colour. Similar observations were reported in buffalo and camel (El-Shafey & Kassab, 2012), buffalo and cattle (Al-AKraa, El-Kasapy, & El-Shafey, 2014), cattle (Raji et al, 2008) and camel (Badawy, 2011;El-Shafey & Sayed-Ahmed, 2012;Ibrahim et al 2019aIbrahim et al , 2019b.…”
Section: Discussionsupporting
confidence: 81%
“…The current study provided a definite visualization of all ligaments of pastern and coffin joints in buffalo including; collateral and palmar ligaments of the pastern joint, as well as distal inter‐digital, dorsal and collateral ligaments of the coffin joint and collateral navicular ligaments. However, these ligaments of pastern and coffin joints have not been recognized in the previous studies in the same animal (Abdellatif et al, ; Al‐Akraa et al, ; El‐Shafey & Kassab, ).…”
Section: Discussionmentioning
confidence: 85%
“…In large animals, CT has been used sparingly for descriptive anatomic research (Hathcock et al 1995;Morrow et al 2000;De Zani et al 2010;Zafra et al 2012) and several studies have demonstrated the clinical value of CT in diagnosing diseases of the head (Tietje et al 1996;Warmerdam et al 1997). In camelids, CT anatomy of the nasal cavity Wang et al 2008), temporomandibular joint (Arencibia et al 2012), tarsus (Hagag et al 2013) and metatarsus and digits (El-Shafey & Kassab 2013) has been studied, but to the author's knowledge, there is no published material describing the results of CT anatomy of the brain and associated structures in dromedary camel applying bone and soft-tissue CT windows.…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies (Badawy, 2011;El Nahas et al, 2015;El-Shafey & Kassab, 2013;Lischer, Walliser, Witzmann, Eser, & Ohlerth, 2005), the anatomical structures of the forelimb digit of the onehumped camel were described and identified using computed tomography (CT) and cadaver sections. The aim of this study focused on the hind fetlock joint using the 3D reconstruction render volume of CT, transverse, sagittal and frontal planes of the CT and digital radiographic images.…”
Section: Introductionmentioning
confidence: 99%